Peran Literasi Keuangan dan Inklusi Keuangan Dalam Meningkatkan Penggunaan Financial Technology Pada UMKM - Tiara Syahrani; Endar Pradesa (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this study was to determine the role of financial literacy and financial inclusion in increasing the use of financial technology in MSMEs in Lubuklinggau City. The research method used is quantitative research where each variable is measured by a Likert scale. The number of samples in this study were 42 respondents, namely culinary MSMEs in Lubuklinggau City. Data collection techniques used in this study were document studies and questionnaires. The data analysis technique uses multiple linear regression with the help of SPSS. The results of the study show that financial literacy has a significant influence on financial technology, this is evidenced by the results of the t-test calculation which shows a significance value of 0.006 <0.05. Financial inclusion has a significant influence on financial technology, this is evidenced by the results of the t-test calculation which shows a significance value of 0.004 <0.05.